Influence of diatomite and its base modifications on the self-adhesive properties of silicone pressure-sensitive adhesives - Adrian Krzysztof Antosik; Karolina Mozelewska; Marlena Musik; Piotr Miądlicki (Scientific Reports, 2023)
Abstract The study examined how diatomite and its modifications affected the self-adhesive ability of silicone pressure-sensitive adhesives. To create adhesive composition for testing, fillers were added to a commercial silicone resin, which were then used to create new modified pressure-sensitive tapes. The resulting tapes were tested to determine their adhesion, tack, cohesion at room and elevated temperature, SAFT test (Shear Adhesive Failure Temperature), pot-life (viscosity) and shrinkage. The results obtained were compared with those of the unmodified tapes. The tests resulted in higher thermal resistance (225 °C) and lower shrinkage (0.1%). As a result, we can conclude that materials with thermal resistance with a slight decrease in other parameters were obtained.